Crystal melting and vitrification behaviors of a three-dimensional nitrile-based metal–organic framework. (26th October 2020) - Das, Chinmoy; Horike, Satoshi
Abstract : A 3D porous MOF containing a tripodal nitrile ligand was found to show crystal melting at 271 °C and vitrification. Abstract : A three-dimensional (3D) metal–organic framework [Ag( p L2)(CF3 SO3 )]·2C6 H6 ( p L2 = 1, 3, 5-tris(4-cyanophenylethynyl)benzene), composed of Ag + and tripodal nitrile ligands, was prepared to enable the investigation of its crystal melting and vitrification behaviors. The guest-free state showed a crystal melting at 271 °C, and the liquid state transformed into a glassy state via cooling. The vitrification of the crystalline compound into an amorphous glassy state was also obtained by mechanical hand-grinding. The structure of the glassy state retained the 3D networked structure, confirmed by FT-IR, X-ray absorption, and scattering measurements. The mechanically induced glass showed a small uptake of CO2 and a strong affinity for benzene and H2 O vapors, confirmed by gas sorption isotherms. Powder X-ray diffraction studies have revealed that the vitrified structure returned to the original 3D crystalline structure by exposure to these vapors.